Bridging Cultures: Javanese and Chinese Community Reconciliation in Krian - Hakam, Dear; Hariyanto, Didik (Indonesian Journal of Cultural and Community Development, 2024)
Background: Increasing interactions between local communities and newcomers highlight the importance of understanding intercultural communication and its societal impacts. Specific Background: This study examines intercultural communication between local residents and migrants, focusing on how these interactions facilitate cultural acculturation. Knowledge Gap: Despite existing literature, research on specific ethnic interactions and their social integration remains limited. Aims: The research aims to explore the dynamics of intercultural communication and acculturation processes within a particular community through qualitative analysis. Results: Findings reveal that both local residents and migrants demonstrate openness, fostering trust and social cohesion through shared experiences. Local residents adapt to migrant customs, particularly in cuisine, while migrants engage with local traditions. Novelty: This study highlights the role of interpersonal relationships in fostering acceptance and cultural blending. Implications: Results emphasize the need for community initiatives that promote intercultural dialogue to enhance social integration and cultural richness, serving as a model for regions facing cultural diversity challenges. Highlights : Openness and trust between local residents and migrants foster social cohesion. Mutual adaptation in customs, particularly in cuisine, enhances cultural exchange. Community initiatives promoting dialogue can strengthen integration in diverse environments. Keywords: intercultural communication, cultural acculturation, social integration, ethnic diversity, community initiatives